Media for History Learning In the Digital Era - Bih Ni Lee (Universitas Ahmad Dahlan, 2022)
Background: In the information age and today's digital age, educators play an important role in shaping good character. Educators have excellent opportunities to develop professional competencies that can be enhanced, one of which is the ability to technically and creatively create innovative learning designs that facilitate educators' ability to optimize students' abilities. Contribution: The contribution of this research is to raise awareness among educators in the digital arena of what is required to develop innovative and creative History learning media. Other matters related to educators' confidence in leveraging technology in History learning also need to be optimized. Method: Synthesis method. Researcher synthesized information naturally to help others see connections between things. Results: The t-test result indicated that the post-test scores were significantly higher for the experimental group (M = 41.71, SD = 2.14) than for the control group (M = 20.41, SD = 4.3), t = 4.130, p < .001. In other words, there was a significant difference in the mean post-test results between the experimental and control groups. As such, Edmodo can positively impact the academic performance of higher education students. When being applied to the experimental and control methods, the ratio was 2.62, which was greater than the reference value (1.2). This showed that Edmodo effectively improved students' study skills and knowledge. Conclusion: The impact of this result can be explained by the fact that Edmodo increased the use of collaborative e-learning in the experimental group to keep students informed. A good website provides students with high-quality information, creativity, participatory activities and collaboration in a category called Social Networking and Communication. The application of digital literacy by utilizing media in History learning can be done by utilizing the existing facilities at Edmodo